2015
DOI: 10.1007/s13361-015-1172-4
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of Mobility-Selected H+-Gly-Pro-Gly-Gly (GPGG)

Abstract: Abstract. We report the first results from a new instrument capable of acquiring infrared spectra of mobility-selected ions. This demonstration involves using ion mobility to first separate the protonated peptide Gly-Pro-Gly-Gly (GPGG) into two conformational families with collisional cross-sections of 93.8 and 96.8 Å 2 . After separation, each family is independently analyzed by acquiring the infrared predissociation spectrum of the H 2 -tagged molecules. The ion mobility and spectroscopic data combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
109
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(117 citation statements)
references
References 64 publications
6
109
0
Order By: Relevance
“…1, in which we couple cryogenic, messenger-tagging spectroscopy in an ion trap with drift-tube IMS-MS [22]. …”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, in which we couple cryogenic, messenger-tagging spectroscopy in an ion trap with drift-tube IMS-MS [22]. …”
Section: Experimental Methodsmentioning
confidence: 99%
“…Both ion mobility spectrometry and cryogenic ion spectroscopy have shown that ions can adopt multiple stable conformations in the gas phase, some of which may be kinetically trapped [22, 3033]. For this reason, we choose to anneal all the conformations produced in the nano-ESI process, driving them to the lowest energy gas-phase structure(s) before measuring the CCS and the vibrational spectrum (see supporting information).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Further, IM-MS can be used to prepare samples for gas-phase IR spectroscopy. [25][26][27][28][29] Here ions are simultaneously mass-tocharge (m/z) selected by MS and specific oligomers are geometrical size selected by IMS. This is in contrast to experiments where only m/z selection is used which can suffer from signal overlap between a cluster and its larger counterpart, which, for example, have twice the mass and twice the charge.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, several advances coupling drift tube IMS and other time-dispersive methods (i.e., traveling wave IMS) to mass spectrometry (MS) [1][2][3][4][5][6][7][8][9][10] have extended its versatility for a range of chemical [11][12][13][14][15][16][17], physical [18][19][20][21][22][23], and biomolecular structural studies [24][25][26][27][28][29][30][31][32][33]. Still relatively new to the biomedical field, several groups have recently begun to incorporate LC-IMS-MS workflows in proteomics studies [34][35][36][37], and enhanced performance has been demonstrated [38].…”
Section: Introductionmentioning
confidence: 99%